THE COMPARISON OF EFFECTIVENESS BETWEEN SPORT MASSAGE AND WORKPLACE STRETCHING-EXERCISE IN REDUCING FATIGUE AND MUSCULOSKELETAL DISORDERS AMONG TAILORS IN PT. ULUWATU GARMENT - Dewi, Ni Made Ida Kristina; Dewi, Anak Ayu Nyoman Trisna Narta; Muliarta, I Made (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Fatigue was the reduce in efficiency and endurance of body condition while working with data collection tools such as 30 fatigue item questionnaire. Musculoskeletal Disorder was the disorder of musculoskeletal pain in upper or lower extremity with data collection tools such as Nordic Body Map questionnaire. This study was an experimental study with the design was Pretest and Posttest Two Group Design, and the amount of sample were 24 people separated into 2 Group with the sport massage and workplace stretching-exercise (WSE) technique in PT. Uluwatu Gament. Data analysis was performed by Paired sample T-test and independent t-test. The result indicated that sport massage could reduce the fatigue and musculoskeletal disorder with the result p=0,000 and WSE could reduce fatigue and musculoskeletal disorder with the result p= 0,001 and p= 0,023; the sport massage better at reduced the fatigue (p<0,05) instead of WSE, and they were both better at reduce musculoskeletal disorder (p>0,05). Keyword : tailor, fatigue, musculoskeletal disorder, sport massage, workplace stretching-exercise(WSE)